Fenomena Glass Ceiling Sebagai Wujud Budaya Patriarki Di Korea Selatan - Saragi, Agnes Monica Stephanie; Agustina, Baiq Nindy Anidia (Pusat Studi Gender Universitas Jember, 2022)
The increased work for women has become one of the most remarkable social transformations in the entire country. As the age grows globally, respecting gender differences and treating women fairly in the workplace becomes increasingly important to achieving equality and social justice for women. Gender equality in the job, seems less prominent in Korea. The study analyzes gender representation and obstacles to the advancement of women's careers in the Korean government. Statistical data reveal that underrepresented women in the Korean government especially at the top. Korean female civil servants have experience in terms of restricted access to the top ranks and obstacles to women's career progress. Cultural differences such as the strong influence of Confucian traditions and collectivism in Korean society may be more challenging for female employees in Korea.